Nurses´ knowledge and expectations regarding the schizofrenic care - Castro, Sueli Aparecida de (2017)
Nurses face difficulties in their practice regarding the implementation of care to the schizophrenic. This article aims to identify the knowledge and activities of the nurse’s team about the schizophrenic care. This study realized in 2004 is the type exploratory-descriptive, with quality-quantitative analysis. Seventeen of 20 nurses of a public hospital participated in the interview, eight specialized in Psychiatric Nursing and the majority prefers to work with chronic patients. Nurses and the nursing team report difficulties in the management of schizophrenic patients with symptoms of heteroagressiveness, delirium, hallucinations and imprevisibility. There are few references regarding the patient’s autonomy and the family participation in the therapeutic procedure. The nurses´ greater difficulty is on communication and interpersonal relations. Concluding, nurses assist the patients according to syntomatology, show concern with the assistance delivered and report the need to seek knowledge.